Preliminary report of the characteristics of the upper thigh spur area of the femoral neck in Garden I and II subcapital fractures - Touloupakis, Georgios; Maione, Alessio; Lettera, Maria Gabriella; Stuflesser, Wilfried; Ferrara, Fabrizio; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2018)
The “heart” of the calcar is the internal cortical septum called “femoral thigh spur”. Nevertheless, the integrity of the femoral thigh spur and its extensions in Garden I and II femoral neck fractures has not been examined in depth, in CT scan-based studies. The aim of this retrospective study is to analyze characteristics as integrity of upper thigh spur area of the intra-capsular femoral neck using precise CT scans, as well as features of the medial cortical bone interruption of orthopedic calcar, in femoral fractures that are radiographically defined as Garden type I-II.A total number of 23 patients was finally included in our study. We called it the “upper thigh spur area” the area around a 360 degree perimeter of the upper thigh spur. The above-mentioned area is a cylindrical intracapsular structure oriented parallel to the intertrocanteric line of the proximal femur . We analyzed the modification of the cortical bone in this specific intra-capsular area of the femoral neck. In all the cases the upper thigh spur area (the internal cortical septum) was intact. The medial cortical (the known “orthopedic calcar”) was evaluated by CT scans in coronal views; it was found to be interrupted in 14 patients and intact in 9; among patients of the first group, 50% were classified as Garden I and 50% as Garden II. The cortical integrity on 360° of the upper thigh spur area was evaluated by CT scans in axial views through different cuts, and it was found to be intact in all cases. More extended studies including CT scans of Garden I-II-III and IV fractures are needed so as to obtain more complete results. In conclusion, it seems that the integrity of the upper thigh spur zone is associated with stable fractures.